Coronary artery bypass grafting versus percutaneous coronary intervention in multivessel coronary artery disease: Indications, outcomes, and survival - Luiz Felipe Baratela Cuzzi; Pedro Lucarelli Gonçalves De Oliveira; Caique Sousa Silva; Isabella Coimbra de Souza Parahyba; Camila Reis Pereira; Daffny Gomes Aguiar (International Health Sciences Review, 2026)
Multivessel coronary artery disease creates a revascularization decision in which procedural invasiveness must be balanced against long-term durability and protection from future ischemic events. This narrative review compares coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) in adults with multivessel disease, emphasizing indications, survival, myocardial infarction, stroke, repeat revascularization, anatomical complexity, and diabetes. A targeted search was conducted in August 2026 in PubMed/MEDLINE and official guideline publications from major cardiovascular societies. Guidelines, randomized trials, extended follow-up studies, meta-analyses, and selected high-quality observational evidence were prioritized. The evidence consistently shows that CABG is more durable, with fewer spontaneous myocardial infarctions and repeat procedures, and that its survival advantage is clearest in complex three-vessel disease and in patients with diabetes when surgical risk is acceptable. Contemporary FFR-guided PCI with current-generation drug-eluting stents has narrowed several differences: in FAME 3, five-year mortality and the composite of death, stroke, or myocardial infarction were not significantly different, although myocardial infarction and repeat revascularization remained more frequent after PCI. PCI provides faster functional recovery and lower early procedural burden. Revascularization strategy should therefore be individualized through Heart Team assessment, integrating anatomy, feasibility of complete revascularization, ventricular function, comorbidities, life expectancy, surgical risk, and patient preferences.